Coaching intervention indices as predictors of effective coaching among Nigerian coaches / Olufemi Adegbesan, A.S Chidi and Oluwatoyin Mercy Jaiyeoba - Olufemi, Adegbesan; A.S, Chidi; Oluwatoyin Mercy, Jaiyeoba (Faculty of Sports Science and Recreation, University Press of Universiti Teknologi MARA, 2020)
The purpose of this research was to investigate on coaching intervention behaviors as predictors of an effective coaching. It was a descriptive research design and correlation type study to gain an in-depth understanding of the participants' views on the coaching intervention and effective coaching practice variables. Participants for this study were 50 male and 34 female athletes with mean age (mean = 24.52; SD 9.4). Athletes with sport involvement liked athletics, judo, swimming, volleyball, handball and table tennis. The measures used were Perceived Coaching Intervention Questionnaire (r =.84) and Effective Coaching Scale (r =.79). The results showed positive correlations between Effective Coaching and Encouragement (r =.514, p<.05), Technical Information (r =.614, p< .05), Negative Feedback (r =.59l , P<.05) Positive feedback (r =.585, p<.05). 46.9% of the variance in the dependent variables was explained by four predictor variables when taken together. Conclusively, it was identified that positive feedback was the most potent from the four interventions as perceived by the athletes. The recognition of these excellent intervention coaching practice along the various sporting pathway would supports developments in models and frameworks for sport in Nigeria and globally.